Efficacy-Based Perspective to Overcome Reduced Opioid Analgesia of Advanced Painful Diabetic Neuropathy in Rats - Balogh, Mihály; Zádor, Ferenc; Zádori, Zoltán S.; Shaqura, Mohammed; Király, Kornél; Mohammadzadeh, Amir; Varga, Bence; Lázár, Bernadette; Mousa, Shaaban A.; Hosztafi, Sándor; Riba, Pál; Benyhe, Sándor; et al. (Frontiers in Pharmacology, 2019)
Reduction of the opioid analgesia in diabetic neuropathic pain (DNP) results from µ-opioid receptor (MOR) reserve reduction. Herein, we examined the antinociceptive and antiallodynic actions of a novel opioid agonist 14-O-methymorphine-6-O-sulfate (14-O-MeM6SU), fentanyl and morphine in rats with streptozocin-evoked DNP of 9-12 weeks following their systemic administration. The antinociceptive dose-response curve of morphine but not of 14-O-MeM6SU or fentanyl showed a significant right-shift in diabetic compared to non-diabetic rats. Only 14-O-MeM6SU produced antiallodynic effects in doses matching antinociceptive doses obtained in nondiabetic rats. Co-administered naloxone methiodide (NAL-M), a peripherally acting opioid receptor antagonist failed to alter the antiallodynic effect of test compounds, indicating the contribution of central opioid receptors. Reduction in spinal MOR binding sites and loss in MOR immunoreactivity of nerve terminals in the spinal cord and dorsal root ganglia in diabetic rats were observed. G-protein coupling assay reveals low efficacy character for morphine and high efficacy character for 14-O-MeM6SU or fentanyl at spinal or supraspinal levels (Emax values). Furthermore, at the spinal level only 14-O-MeM6SU showed equal efficacy in G-protein activation in tissues of diabetic- and non-diabetic animals. Altogether, the reduction of spinal opioid receptors concomitant with reduced analgesic effect of morphine may be circumvented by using high efficacy opioids, which provide superior analgesia over morphine. In conclusion, the reduction in the analgesic action of opioids in diabetic neuropathic pain might be a consequence of MOR reduction, particularly in the spinal cord. Therefore, developing opioids of high efficacy might provide analgesia exceeding that of currently available opioids.